IllumiRoom: Peripheral Projected Illusions for Interactive Experiences - Jones, Brett; Benko, Hrvoje; Ofek, Eyal; Wilson, Andy (CHI '13 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2013)
IllumiRoom is a proof-of-concept system that augments the area surrounding a television with projected visualizations to enhance traditional gaming experiences. We investigate how projected visualizations in the periphery can negate, include, or augment the existing physical environment and complement the content displayed on the television screen. Peripheral projected illusions can change the appearance of the room, induce apparent motion, extend the field of view, and enable entirely new physical gaming experiences. Our system is entirely self-calibrating and is designed to work in any room. We present a detailed exploration of the design space of peripheral projected illusions and we demonstrate ways to trigger and drive such illusions from gaming content. We also contribute specific feedback from two groups of target users (10 gamers and 15 game designers); providing insights for enhancing game experiences through peripheral projected illusions.